Effect of twisted ratio on flow structure, heat transfer and thermal improvement in a circular tube with single twisted tape - Jedsadaratanachai, Withada; Boonloi, Amnart (My University, 2013)
The research presents a numerical analysis of laminar fully developed periodic flow and heat transfer in a constant temperature-surfaced circular tube with single twisted tape inserted. The twisted tape is introduced and inserted in the middle of the tested tube. The effects of twisted ratios (y/W = 1, 2, 3, 4, 5 and 6) are presented for Reynolds number (Re) values ranging from Re = 100 to 2000. The SIMPLE algorithm and periodic condition are used in the current study. The computational results are shown in the topology of flow, heat transfer and thermal improvement. It is found that the heat transfer in the circular tube with the twisted tape is more effective than that with no twisted tape inserted. The increase in the y/W ratio leads to decrease in the Nusselt number and friction factor. In addition, the numerical result shows that the reduction in the y/W ratio not only helps to create strong longitudinal vortex flows which enhance heat transfer, but also increase the pressure loss in the tested tube. The computed result reveals that the maximum value of the thermal enhancement factor, TEF is found to be 3.52 for using the twist tapes with y/W = 5 at the highest Reynolds number regime. © 2014 Science Publications.
Keywords: Heat transfer; Laminar flow; Periodic flow; Pressure loss; Tube; Twisted tape